Gyrotron at the second harmonic of the cyclotron frequency AND WORKING MODE H06 - S. V. Kolosov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Modeling processes in gyrotron showed that it is possible to create millimeter gyrotron operating at the second harmonic of the cyclotron frequency with an efficiency of over 27 %. Ohmic losses increasing process in the resonator walls advancing into the submillimeter wavelength range were analyzed. To advance millimeter and submillimeter wavelength range should use higher wave types to reduce energy losses in the waveguide walls or use superconducting resonators, for example, niobium.